ANALYSIS OF FACTORS AFFECTING THE COMPLIANCE OF UMKM TAXPAYERS IN KLAMBIR LIMA KEBUN, HAMPARAN PERAK DISTRICT - Rioni, Yunita Sari; Fachruddin, Wan; Damanik, Destari (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study aims to analyze the effect on taxpayer compliance .    This research was conducted using primary data with a questionnaire. The data analysis technique used in this study is Multiple Linear Regression, which is operated through the SPSS program. Hypothesis testing with t-test shows that the variable Awareness Taxpayers have no significant effect on Taxpayer Compliance. Whereas Understanding of Tax Regulations, and the Level of Trust of Taxpayers in the System Government has a significant effect on taxpayer compliance .